Journal podcasting of health and medical science - Greeves, Scott; Ledbetter, Rhesa; McGovern, Rachel; Wiley, Keith (Frontiers in Communication, 2025)
Podcasts are a growing medium of mass communication and are increasingly being produced by academic journals. However, little is known about the specific features of these journal-affiliated podcasts, particularly in the health and medical sciences. This study examines the characteristics and features of journal podcasts through a content analysis of 400 episodes from 10 highly indexed journals. Using a quota sampling method, we analyzed the 40 episodes from each series. A systematic coding approach was employed to assess eight key variables, including host type, guest composition, topic, communication format, complexity, and audio quality. Findings reveal that the majority of episodes focus on research published within the parent journal and are primarily hosted by researchers. The prevalent communication format was scientific, with minimal use of narrative or emotive styles. This study represents an initial investigation into the emerging niche of journal podcasts and identifies opportunities for future research to further understand their role in the media ecosystem and to broaden public engagement with scientific research.